The Variance of Strong Acid and Long Time Soaking Solutions on Quality of pH and Protein Gelatin of Sheep Skin - Muhamad Hasdar; Yuniarti Dewi Rahmawati (Fakultas Pertanian Universitas Veteran Bangun Nusantara Sukoharjo, 2017)
This study aims to determine the quality of pH and sheep skin gelatin protein that is hydrolyzed using strong acid. The main ingredient of this research is sheep skin originated from Brebes Regency which is 1 - 2 years old. The research method used Randomized Completely Randomized Design (RAL) 2 x 3 factorial pattern where the first factor is soaking material (HCl 2% v / v and H2SO4 2% v / v) and second factor is the duration of immersion (2 hours, 3 hours and 4 hour), then continued with the real difference test using Duncan Multiple Range Test (DMRT). The test results showed sheep skin gelatin value that is pH 3,52 - 3,85 and protein 88,80 - 90,47%. HCl 2% ability to hydrolyze sheep skin collagen is better than 2% H2SO4. Highest pH and protein values occur at 4 hours of soaking time.